Drainage system evaluation and control of inundation in campus and housing areas of ITS, Surabaya - Alvin, Eldo Fikri; Mardyanto, Mas Agus (Centre for Science and Technology, IAIN Surakarta, 2017)
The campus area of Sepuluh November Institute of Technology (Institut Teknologi Sepuluh Nopember/ITS) and its housing complex are usually inundated during heavy rain. It is because the slope of the land of the campus area is generally flat. Moreover, some of the existing drainage channels also contain sediment thus reducing the optimum capacity of the channels. Hence, an evaluation of ITS’s drainage system needs to be conducted. This evaluation was undertaken in stage with the following steps: identification of the existing problems, collection of primary and secondary data, literature review, calculation of the capacity of the existing channels, calculation of run-off, and analysis of the existing retention ponds. The primary data included the flow direction, the slope and dimensions of the channels, and thickness of sediment in the channels. The secondary data comprised rainfall intensity, ITS master plan, and land use. The calculation included the engineering design, the bill of quantity (BOQ), and budget. A standard operating procedure for drainage system maintenance to make the channels optimum was also suggested. From the analysis, it is shown that the maximum daily rainfall is 136.09 mm/day for a 5 year-rainfall return period and 159.19 mm/day for a 10 year-rainfall return period. Inundation around ITS is resulted from some channels which are not connected to each other making drainage water unable to flow easily to the receiving water body (river). Another cause of such inundation is the slope of some channels that were not made properly. The inundation of some roads occurs because of the absence of street inlets, resulting in the water unable to flow to the side channels. It can be concluded that in some areas, the number of secondary channels and box culverts needs to be added, the slope of some channels needs to be rearranged, and a total of 288 street inlets must be constructed along the planning area.